Industrial 5G based digital twin control platform for flexible intelligent manufacturing - Yaoqi LIU; Hongguang LI; Yiqing ZHOU; Jinglin SHI; Yingjiao MA; Manli QIAN (Dianxin kexue)
As the key of intelligent manufacturing, industrial Internet deeply integrates advanced manufacturing technology with industrial 5G.It runs through all links of the whole life cycle, such as material preparation, production and manufacturing, test and service.Facing the increasing demand for customization, small batch production line and deterministic and reliable communication requirements, a industrial 5G based flexible intelligent manufacturing twin control platform was proposed and designed.Specifically, it included flexible manufacturing line with flexible arrangement and on-demand production, intelligent network with industrial 5G with low delay and high reliability as the core, the digital twin control platform of data acquisition and real-time feedback.The platform combined intelligent decision mechanism to realize the closed-loop evolution of perception analysis decision execution.